Community Empowerment Through Utilization of Moringa (Moringa Oleifera Lam.) Plants as Nutritious Food In Balombong Village, Pamboang District, Majene Regency, West Sulawesi Province - Ramlah Ramlah; Arlinda Puspita Sari; Yusrianto Nasir; Haerani Haerani (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2023)
Moringa (Moringa Oleifera Lam.) is a functional food with high nutritional value that thrives and has long been domesticated by people in Balombong Village, Pamboang District, Majene Regency, West Sulawesi Province. This activity aims to provide education, and introduce moringa-based processed products. The method of community service activities (PKM) uses training, and assistance related to the use of moringa plants as nutritious food. This activity was attended by 29 participants from among housewives and 5 students from the Universitas Sulawesi Barat (UNSULBAR). The PKM activities are carried out by disseminating the content of nutritional value, benefits for health, and introducing various moringa-based processed food products such as moringa meatballs, noodles, tea, pudding, chips, pukis, candies, and nuggets. Furthermore, involving all participants in processing one of the food products, namely moringa meatballs. Utilization of moringa can help people improve family health. In addition, processed moringa can be used as Usaha Mikro Kecil dan Menengah (UMKM) products so that they can add to the economy of rural communities. The evaluation results showed that the community service activities carried out had a positive influence on the participants. This can be seen from the percentage value which reached 91.3% of the participants, expressed their strong agreement with the training activities carried out. Most of the participants also revealed that the PKM activities were able to improve the learning experiences and skills.